2009
DOI: 10.1080/00016480802552550
|View full text |Cite
|
Sign up to set email alerts
|

A zinc-containing compound, Polaprezinc, is effective for patients with taste disorders: randomized, double-blind, placebo-controlled, multi-center study

Abstract: The group of patients given 68 mg zinc showed a significant improvement in their gustatory sensitivity compared with the placebo group. The most common side effects observed were increase in serum triglyceride and serum alkaline phosphatase, decrease in serum iron, and some gastrointestinal incidents, although they were not serious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 18 publications
1
44
5
Order By: Relevance
“…1), has an anti-ulcer effect and is used clinically for the treatment of gastric ulcer in Japan (Matsukura and Tanaka 2000). Recently, Sakagami et al reported that polaprezinc improved hypogeusia without serious side effects in a well-controlled doubleblind clinical study (Sakagami et al 2008). We have also reported that polaprezinc ameliorated abnormalities of taste sensation in zincdeficient rats (Hamano et al 2006).…”
Section: Introductionsupporting
confidence: 58%
“…1), has an anti-ulcer effect and is used clinically for the treatment of gastric ulcer in Japan (Matsukura and Tanaka 2000). Recently, Sakagami et al reported that polaprezinc improved hypogeusia without serious side effects in a well-controlled doubleblind clinical study (Sakagami et al 2008). We have also reported that polaprezinc ameliorated abnormalities of taste sensation in zincdeficient rats (Hamano et al 2006).…”
Section: Introductionsupporting
confidence: 58%
“…It would be worthwhile to investigate in further studies if IBD patients with reduced olfactory and gustatory functions have improvements in their quality of life and in nutritional behavior when adding small amounts of herbs and spices (trigeminal input), glutamate, or other flavors to their foods [34][37]. Perhaps taste could be improved by prescribing oral zinc [38], [39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated by a double‐blinded control clinical trial that PZ improves the disease conditions of idiopathic taste disorders 32. It has also been shown that zinc sulfate prevents taste alterations associated with radiation in patients with head and neck cancer,33 although inconsistent result showing no preventive effect of zinc sulfate against radiation‐induced taste alteration was also reported 34.…”
Section: Discussionmentioning
confidence: 99%